Problems of ukrainian school youth in the conditions of forced migration: Sociological dimensions - Hlebova, Natalia; Afanasieva, Lyudmila; Bukrieieva, Iryna; Glyns'ka, Lyudmila; Murtaziiev, Ernest (Eduweb, 2023)
The purpose of the study is to analyze the sociological analysis of Ukrainian schoolchildren's attitudes towards the educational environment, learning conditions and current problems of adaptation in countries of temporary residence. The methodology used is an interdisciplinary approach that allows to integrate knowledge of different branches of science about the subject to form a holistic picture of the study. The empirical basis of the article is based on the materials of a sociological study of the educational environment, learning conditions and current problems of adaptation "Forced migration 2022 in the eyes of Ukrainian schoolchildren", conducted by an online survey. It is found that European education systems have responded to the challenges at the state level: they adopt regulations, send out recommendations and manuals for teachers, solve the problems of informatization of education, provide schools with specific tools, and increase the number of teachers. It is established that the main problems of schoolchildren abroad are: language barrier; significant differences in educational programs in Ukrainian and foreign institutions; double load (studying in a Ukrainian and foreign educational institution); imperfect informatization of education; multi-age classes in schools of the host country; studying new subjects for Ukrainian schoolchildren.